Accuracy in Estimation of Blood Loss Using the SAPHE (Signaling a Postpartum Hemorrhage Emergency) Mat [51]. (May 2015) - Wilcox, Lorine Lieslle; Ramprasad, Chethan; Gutierrez, Amanda; Oden, Maria; Richards-Kortum, Rebecca; Gandhi, Manisha
Abstract : INTRODUCTION: To validate the accuracy of the SAPHE (Signaling a Postpartum Hemorrhage Emergency) Mat in estimating blood loss after vaginal delivery. METHODS: The SAPHE Mat, developed by a team of students at Rice University, is comprised of super absorbent polymer, nylon, pellon, and surgimat dressings. The mat was constructed so that each square on the mat would absorb up to 50 cc of blood. Twenty-six patients, recruited from October 2013 to July 2014, underwent vaginal delivery using the SAPHE Mat. Visual estimation of blood loss using the SAPHE Mat was calculated by multiplying the number of blood-saturated squares or partial squares by 50 cc. Accuracy of this visual estimate (visual EBL) was compared with the actual blood loss calculated from the difference in weight of the SAPHE Mat in grams before and after use (volume blood loss). RESULTS: Visual EBL estimations were within 100 cc of the volume blood loss 70% of the time and within 200 cc 90% of the time. The mean difference between the visual EBL and volume blood loss was 74 cc, with a standard deviation of 62 cc. The Pearson correlation coefficient for visual EBL and volume blood loss was positive at 0.96 ( P <.001). CONCLUSION: The SAPHE Mat is accurate in providing an estimation of blood loss after vaginal delivery. Future studies will assess the ability to deploy the SAPHE Mat in low-resource settings as a potential guide for estimating blood loss to assist in determining the need for administration of misoprostol or timely transfer of the patient to a higher care facility.